Las ciudades y el cambio climático: el caso de la política climática de la Ciudad de México - Quiroz Benítez, Diana Esmeralda (El Colegio de México A.C., 2013)
This study analyzes the climate policy of Mexico City. It describes the emergence of the national and international institutional framework and subsequently explores the characteristics of the Federal District regarding to emissions and vulnerability as a context for presenting and analyzing the mitigation and adaptation strategies established in the Mexico City Program for Climate Change 2008-2012. It also mentions some of the constraints that prevent this program from being achieved and contributing to the solution of the problem of climate change at the local and international level.